2012
DOI: 10.1124/dmd.111.044420
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Cassette-Dosing Approach to Assess Brain Penetration in Drug Discovery

Abstract: ABSTRACT:The objective of the present study was to examine the cassette dosing method in determination of brain-to-plasma concentration ratio (area under the concentration-time profiles for plasma/area under the concentration-time profiles for brain, K p ). Eleven model compounds, amprenavir, citalopram, digoxin, elacridar, imatinib, (3S,6S,12aS)-1,2,3,4,6,7,12,12a-octahydro-9-methoxy-6-(2-methylpropyl)-1,4-dioxopyrazino[1,2:1,6]pyrido[3,4-b]indole-3-propanoic acid 1,1-dimethylethyl ester (Ko143), loperamide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 30 publications
6
35
1
Order By: Relevance
“…3). Testing Ko143 in vivo was outside the scope of our own study, but Liu et al (2012b) found that, although the brain concentration of Ko143 was below the lower limit of detection in wild-type mice following a 3 mg/kg Ko143 dose, it was approximately three times higher in Abcb1a/bknockout and Abcb1a/b/Abcg2-knockout mice than in Abcg2-knockout mice. Based on this, the authors hypothesized that Ko143 was a dual substrate of ABCG2 and ABCB1 (Liu et al, 2012b).…”
Section: Discussionmentioning
confidence: 81%
“…3). Testing Ko143 in vivo was outside the scope of our own study, but Liu et al (2012b) found that, although the brain concentration of Ko143 was below the lower limit of detection in wild-type mice following a 3 mg/kg Ko143 dose, it was approximately three times higher in Abcb1a/bknockout and Abcb1a/b/Abcg2-knockout mice than in Abcg2-knockout mice. Based on this, the authors hypothesized that Ko143 was a dual substrate of ABCG2 and ABCB1 (Liu et al, 2012b).…”
Section: Discussionmentioning
confidence: 81%
“…We also examined the brain to plasma and liver to plasma concentration ratio (or Kp ratio = brain/plasma or liver/ plasma) to get a measure of tissue exclusion or retention (Kalvass et al, 2007a;Liu et al, 2012). Consistent with previous results (Wang et al, 2004), the adult brain K P ratio for 6b-naltrexol was 0.13 (units 5 ml/g) at 20-minute survival (P , 0.0001 for difference from unity) and 0.34 at 45-minute survival (P , 0.0001 for difference from unity; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the extreme potency of 6b-naltrexol to block withdrawal behaviors in juvenile mice. The mechanism by which 6b-naltrexol is largely excluded from the brain by a mature BBB remains to be determined, but likely involves the main efflux transporters Mdr1 and Bcrp1 genes (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These 11 compounds were selected to create the "worst-case" scenario of potential drug-drug interactions at the BBB as this group of compounds contains known potent P-gp and Bcrp inhibitors and typical P-gp and Bcrp substrates. However, no drug-drug interactions at the BBB were observed in our previous study in mice when these 11 compounds were dosed in a cassette at 1-3 mg/kg (Liu et al, 2012). We hypothesized that plasma concentrations generated after a cassette dosing at 1-3 mg/kg for each compound were too low to cause any significant drug-drug interactions at the BBB.…”
Section: Introductionmentioning
confidence: 84%
“…The common method of estimating K p,uu,brain is to determine the in vivo plasma and brain concentration ratio (K p ) and the in vitro unbound fraction in plasma and brain tissue (Kalvass and Maurer, 2002). To increase the throughput and reduce resource consumption in determination of K p , we demonstrated in a previous study that cassette dosing (dosing a mixture of compounds) generated similar K p values to discrete dosing (dosing an individual compound) for 11 compounds,namely,amprenavir,citalopram,digoxin,elacridar,imatinib,Ko143 [(3S,6S,2,3,4,6,7,12,29:1,6]pyrido [3,4-b]indole-3-propanoic acid 1,1-dimethylethyl ester], loperamide, prazosin, quinidine, sulfasalazine, and verapamil in mice (Liu et al, 2012). The 11 compounds in this study can be classified into four groups according to our previous results (Liu et al, 2012): 1) non-P-gp substrate: citalopram; 2) P-gp substrates: amprenavir, digoxin, loperamide, quinidine, and verapamil; 3) Bcrp substrates: sulfasalazine; and 4) P-gp/Bcrp dual substrates elacridar, imatinib, and prazosin.…”
Section: Introductionmentioning
confidence: 91%